2008
DOI: 10.1016/j.jacc.2008.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived n-3 Fatty Acids and Atherosclerosis in Japanese, Japanese-American, and White Men

Abstract: Objectives To examine whether marine-derived n-3 fatty acids (FAs) are associated with less atherosclerosis in Japanese than Whites in the United States. Background Marine-derived n-3 FAs at low levels are cardioprotective through their anti-arrhythmic effect. Methods A population-based cross-sectional study in 281 Japanese, 306 White, and 281 Japanese American men aged 40–49 was conducted to assess intima-media thickness of the carotid artery (IMT), coronary artery calcification (CAC), and serum FAs. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(219 citation statements)
references
References 42 publications
6
209
0
4
Order By: Relevance
“…Similar results were obtained in two recent studies in Japan (45). The Japan Eicosapentaenoic Acid Lipid Interventions Study (JELIS), a randomized trial of 18,645 Japanese subjects that examined the effectiveness of 1.8 g eicosapentaenoic acid per day plus a statin in reducing CHD rates, and the Japan Public Health Center-Based Study (JPHC), a 10-year prospective cohort study of 41,578 middle-aged Japanese subjects that examined dietary intake of marine-derived n-3 fatty acids; both concluded that marine-derived n-3 fatty acids have protective effects against nonfatal coronary events.…”
Section: Marine Fatty Acidssupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained in two recent studies in Japan (45). The Japan Eicosapentaenoic Acid Lipid Interventions Study (JELIS), a randomized trial of 18,645 Japanese subjects that examined the effectiveness of 1.8 g eicosapentaenoic acid per day plus a statin in reducing CHD rates, and the Japan Public Health Center-Based Study (JPHC), a 10-year prospective cohort study of 41,578 middle-aged Japanese subjects that examined dietary intake of marine-derived n-3 fatty acids; both concluded that marine-derived n-3 fatty acids have protective effects against nonfatal coronary events.…”
Section: Marine Fatty Acidssupporting
confidence: 93%
“…Kromann and Green (44) further reported that acute MI rates in this same population were markedly lower than those in Denmark. Sekikawa et al (45) studied 281 Japanese born and living in Japan, 306 white Americans living in the USA, and 281 JapaneseAmerican men, i.e., Japanese men born and living in the USA, ages 40 to 49 years, regarding marine fatty acid consumption and atherosclerosis incidence. Japanese men had the lowest levels of atherosclerosis, whereas whites and Japanese Americans had similar levels.…”
Section: Marine Fatty Acidsmentioning
confidence: 99%
“…10 The reduced atherosclerotic burden seen in Japanese subjects appears to be due to their higher intake of omega-3 fatty acids. 23 Three major (N > 6000 patients) randomized controlled trials with omega-3 fatty acids have shown significant reductions in either total mortality 24,25 or major adverse cardiac events. 26 Hence, higher tissue levels of omega-3 fatty acids are cardioprotective.…”
Section: Discussionmentioning
confidence: 99%
“…docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) (Omacor/Lovaza 4 g/day) versus placebo in subjects with a high level of erythrocyte DHA enrichment. 7 Furthermore, studies from other groups have shown a positive association between high dietary intake of n-3 PUFAs and less carotid atherosclerotic plaque burden, 8 as well as a plaque-stabilizing effect on carotid atheroma and improved arterial elasticity with n-3 PUFA treatment. 9,10 The aims of this prespecified substudy of the WELCOME (Wessex Evaluation of fatty Liver and Cardiovascular markers in NAFLD with OMacor thErapy) trial 11 were: (i) to investigate the effects of high-dose n-3 PUFA treatment over 18 months on carotid IMT progression in NAFLD subjects and (ii) to describe associations between changes in markers of NAFLD disease severity (both in terms of simple steatosis and steatohepatitis) and carotid IMT progression over that time period.…”
Section: Introductionmentioning
confidence: 99%